2017
DOI: 10.2967/jnumed.117.191981
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT Optimizes Treatment in Staphylococcus Aureus Bacteremia and Is Associated with Reduced Mortality

Abstract: Metastatic infection is an important complication of bacteremia (SAB). Early diagnosis of metastatic infection is crucial, because specific treatment is required. However, metastatic infection can be asymptomatic and difficult to detect. In this study, we investigated the role ofF-FDG PET/CT in patients with SAB for detection of metastatic infection and its consequences for treatment and outcome. All patients with SAB at Radboud University Medical Center were included between January 2013 and April 2016. Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
110
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(118 citation statements)
references
References 23 publications
7
110
0
1
Order By: Relevance
“…Compared with matched historical controls for whom no 18-FDG-PET/CT was performed, a significantly higher number of metastatic infectious foci were diagnosed in the study group (67.8% vs 35.7%, P<0.01), and the mortality rate at 6 months was lower (19.1% vs 32.2%, P=0.014) 21. A 2017 study from the Netherlands found that 18 F-FDG PET/CT detected metastatic infectious foci in 73 of 99 patients with high-risk SAB, 71.2% of which were asymptomatic 22 . 18 F-FDG PET/CT led to treatment modifications in 74 of the 99 high-risk patients and 3-month mortality was lower compared with those who did not undergo 18 F-FDG PET/CT (12.4% vs 32.7%, P=0.003) 22.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Compared with matched historical controls for whom no 18-FDG-PET/CT was performed, a significantly higher number of metastatic infectious foci were diagnosed in the study group (67.8% vs 35.7%, P<0.01), and the mortality rate at 6 months was lower (19.1% vs 32.2%, P=0.014) 21. A 2017 study from the Netherlands found that 18 F-FDG PET/CT detected metastatic infectious foci in 73 of 99 patients with high-risk SAB, 71.2% of which were asymptomatic 22 . 18 F-FDG PET/CT led to treatment modifications in 74 of the 99 high-risk patients and 3-month mortality was lower compared with those who did not undergo 18 F-FDG PET/CT (12.4% vs 32.7%, P=0.003) 22.…”
Section: Discussionmentioning
confidence: 83%
“…A 2017 study from the Netherlands found that 18 F-FDG PET/CT detected metastatic infectious foci in 73 of 99 patients with high-risk SAB, 71.2% of which were asymptomatic 22 . 18 F-FDG PET/CT led to treatment modifications in 74 of the 99 high-risk patients and 3-month mortality was lower compared with those who did not undergo 18 F-FDG PET/CT (12.4% vs 32.7%, P=0.003) 22. Although we considered PET/CT and tagged WBC imaging modalities, we chose tagged WBC based on our desire to maximise test specificity in the setting of a high pretest probability of an undrained source of infection, particularly in a patient with concern for osteomyelitis (in the setting of toe dry gangrene) and presence of a vascular graft—two clinical scenarios where tagged WBC imaging is thought to be useful 23 24…”
Section: Discussionmentioning
confidence: 99%
“…For example, optimal duration of treatment for endocarditis caused by methicillin-susceptible S. aureus may be shorter than for that caused by MRSA [136]. Similarly, although 7-10 days of therapy is appropriate for treatment of uncomplicated gram-negative bacteremia in immunocompetent hosts [137,138], uncomplicated S. aureus bacteremia requires a longer course of therapy to effect cure [139][140][141], likely because of unrecognized seeding [142]. Integrity of host immunity may also affect clearance of infection, so antimicrobial therapy for infection in neutropenic pediatric patients with cancer is often continued until resolution of neutropenia [78].…”
Section: We Recommend Determining the Duration Of Antimicrobial Theramentioning
confidence: 99%
“…St aphylococcus aureus bacteremia (SAB) is a serious infection, associated with a 30-d overall mortality of 20% (1). Metastatic infection, occurring in 16%-73% of patients, is the most important determinant of morbidity and mortality (2)(3)(4)(5)(6)(7)(8). Prolonged bacteremia, delayed clinical response to antibiotic treatment, and the presence of foreign body materials are associated with a complicated course.…”
mentioning
confidence: 99%